Chemical, cellular & clinical aspects of adverse drug reactions. - Park, Brian Kevin (My University, 2014)
Se trata de la primera conferencia organizada dentro del CICLO DE CONFERENCIAS DEL IBIMA titulada “CHEMICAL, CELLULAR & CLINICAL ASPECTS OF DRUG HYPERSENSITIVITY”. Será impartida por el Prof. B. Kevin Park (Professor of Pharmacology. Head of the Institute of Translational Medicine at the University of Liverpool & Director of the MRC Centre for Drug Safety Sciences)
Keywords: Alergia a los medicamentos; Dili; Pharmacology